1995
DOI: 10.1037/0022-006x.63.4.672
|View full text |Cite
|
Sign up to set email alerts
|

Change in coordination across phases of psychotherapy and outcome: Two mechanisms for the role played by patients' contribution to the alliance.

Abstract: This article investigated the mechanisms underlying associations between patients' contribution to the alliance and outcome by examining relations between change in the alliance over the course of treatment and improvement in Short-Term Dynamic Psychotherapy (STDP) and Brief Adaptive Psychotherapy (BAP). Findings for STDP were consistent with 1 model about the role played by the alliance, according to which change in the alliance over the course of therapy is the vehicle for overall improvement. Results for BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 13 publications
1
32
1
1
Order By: Relevance
“…Surprisingly we did not replicate the findings from Westerman et al [16] concerning the relation between PCS and outcome. This may be explained by differences concerning the treatment and the sample.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Surprisingly we did not replicate the findings from Westerman et al [16] concerning the relation between PCS and outcome. This may be explained by differences concerning the treatment and the sample.…”
Section: Discussioncontrasting
confidence: 56%
“…The validity studies of Westerman et al [10,16] showed acceptable interrater reliability (r ranging from 0.68 to 0.93) and good internal consistency (α ranging from 0.63 to 0.98). Coordination measured at intake interview was predictive of outcome (r = 0.60) for a 10-session brief action-oriented therapy.…”
Section: Patient Coordination Stylementioning
confidence: 99%
See 2 more Smart Citations
“…De fato, diversas pesquisas têm demonstrado que a aliança terapêutica é um importante preditor de resultados terapêuticos em diferentes psicoterapias [31][32][33] . Não há ainda, no entanto, estudos suficientes para esclarecer como tais fatores, específicos ou comuns, contribuem para a mudança em psicoterapia 34 .…”
Section: Introductionunclassified